Prospects for the application of radiomics to brain tumors - Olga S. Regentova; Roman A. Parkhomenko; Nikolay I. Sergeyev; Vladimir K. Bozhenko; Pavel V. Polushkin; Vladimir А. Solodkiy (Digital Diagnostics)
Radiomics is a new branch in diagnostics based on a quantitative approach to medical imaging able to ensure more efficient use of medical equipment, optimize imaging time per patient, and increase the accuracy of differential diagnostics in various areas of medicine. Radiogenomics is a branch of radionics intended to establish a connection between the patient’s genotype and phenotypic presentation obtained from medical imaging. The review dwells on general issues for radiomics and radiogenomics in oncology with the recent study findings, focusing on the role of these methods in neurooncology and solving problems in diagnosing brain tumors. One of the current topics in neurooncology is disease prognosis in patients with unverified midline gliomas because morphological confirmation of the diagnosis and molecular genetic testing of tissues is impossible. Besides, the high spatial and temporal heterogeneity of malignant neoplasms prevents a complete assessment of the biological properties of the tumor and even using stereotactic biopsy methods. Radiomics methods can help doctors differentiate the tumor grade, acting as a “virtual biopsy” while avoiding invasive procedures. The study findings on radiomics and radiogenomics in neurooncology indicate the undeniable promise of these methods; however, as in other areas of medicine and biology, errors cannot be completely excluded, so the expert team must aim to minimize them.